2019
DOI: 10.3390/ijerph17010036
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Body Mass Index in Defining Childhood Obesity: Analysis of Cross-Sectional Data from Ghanaian Children

Abstract: Background: Screening methods for childhood obesity are based largely on the published body mass index (BMI) criteria. Nonetheless, their accuracy in African children is largely unknown. The diagnostic accuracies of the World Health Organization (WHO), the Centers for Disease Control and Prevention (CDC), and the International Obesity Taskforce (IOTF) BMI-based criteria in defining obesity using deuterium dilution as a criterion method in a sample of Ghanaian children are presented. Methods: Data on anthropome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Based on WHtR as reference, pBMI was less sensitive (54.0%) to identifying obesity but was highly specific (97.5%) in discriminating non-obese adolescents in the population. This finding corroborates previous studies that have shown low sensitivity of pBMI in screening obesity in Ghanaian children when percentage of body fat was used as reference [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Based on WHtR as reference, pBMI was less sensitive (54.0%) to identifying obesity but was highly specific (97.5%) in discriminating non-obese adolescents in the population. This finding corroborates previous studies that have shown low sensitivity of pBMI in screening obesity in Ghanaian children when percentage of body fat was used as reference [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…The IOTF and WGOC cut-offs, recommended for Asian and Chinese populations, respectively, were included. Although many studies used different BMI-based cut-offs such as WHO, IOTF and WGOC to describe the prevalence of childhood obesity, a small number of articles have carried out comparative studies among three or four sets of BMI cut-offs and drawn different conclusions for racial/ethnic groups (24)(25)(26)(27)(28)(29) . However, few studies made in-depth work on the performances of various BMI cut-offs and examine whether they differ by sex and age groups.…”
mentioning
confidence: 99%
“…The IOTF sample did not have any data from African countries, which was applied in the MULT BMI reference, making the MULT BMI reference the one with the most ethnically diverse sample (Cole et al, 2000). Regarding the applicability of IOTF BMI reference in Africans, a study using the deuterium dilution method to assess nutritional status in school-aged children from Ghana showed that IOTF growth charts did not achieve optimal rates for detecting obesity, presenting high rates of misclassification for the Ghanaians (Adom et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of older data collected from 1963 to 1974 and only from one population (United States) made the WHO 2007 growth charts for school‐aged children (from 5 years old) inaccurate for worldwide use (de Oliveira et al, 2022). Asian and African countries such as China, Pakistan, Iran, and Ghana have found greater divergences when comparing their growth patterns to the ones from WHO 2007, and studies conducted in European countries such as Slovakia, Italy, Poland and Portugal indicate the use of the IOTF BMI reference instead of the WHO growth reference for BMI (2007), as it screened overweight and obesity conditions better in their populations (Adom et al, 2020; Iftikhar et al, 2018; Ma et al, 2010; Minghelli et al, 2014; Mohammadi et al, 2020; Valerio et al, 2017; Woźniacka et al, 2018).…”
Section: Discussionmentioning
confidence: 99%